Heavy metal concentration of sediment in Sungai Tiram Laut at Matang Mangrove Forest, Perak - W. Zainy, Wan Norsuriani (2018)
Mangrove forests thrive near the mouths of large rivers where river deltas provide lots of sediment (sand and mud). Mangrove roots collect sediments and slow the water's flow, helping to protect the coastline and preventing erosion. Over time, the roots can collect enough debris and mud to extend the edge of the coastline further out. The objective of this study was to compare physiochemical properties in Sungai Tiram Laut and compared heavy metal concentration between selected stations and sediment depths. The selected properties in this study were sediment texture using hydrometer method, electrical conductivity using EC meter, sediment pH was identified using pH water and pH KCl, and heavy metal concentration (Fe, Cu, Cd, Pb, Zn) using Aqua Regia method. Data obtained by using statistical analysis system (SAS) version 9.4. Heavy metal contamination was less concentrated except Cu due to maximum permissible addition (MPA) for sediment. The quality standard for Cu was not less than 0.116 cmol/kg. However there was a significant difference concentration by station, but not by depths. The percentage of the sand was higher than silt and clay and had significant difference by stations and depths. Electrical conductivity was higher at location that was nearby to the seawater as caused by the ions in the runoff to the Sungai Tiram Laut. Physiochemical properties concentrated were caused by natural and anthropogenic resources.